Qualitative Study: Compliance with the Implementation of Covid-19 Health Protocols at Jambi City Tourist Attractions - Hubaybah; Fitria Eka Putri; Muhammad Rifqi Azhary; Fadzlul (Journal of International Multidisciplinary Research, 2024)
The Corona Virus Disease 2019 (Covid-19) pandemic was first known to have appeared in Wuhan City, China in December 2019 and was declared a global pandemic by the World Health Organization (WHO) on March 12 2020. This virus has spread very quickly to several countries in the world, including Indonesia where the Covid-19 pandemic has been designated as a type of disease that causes a Public Health Emergency on March 31 2020. With this determination, mitigation efforts must be carried out in accordance with statutory regulations in emergency response period for handling Covid-19. Tourist attractions have the potential to become a locus for the spread of COVID-19 if there is a gathering of visitors while traveling, causing the need for health protocols in carrying out activities at that location. This research uses qualitative research which aims to gather information about the compliance of people at tourist attractions with the health protocols implemented in Jambi City. The results of this research show that the implementation of the health protocol, namely 5M (wearing a mask, washing hands, maintaining distance, staying away from crowds and reducing mobility) is carried out well and is carried out directly by the government and tourist attraction owners through CHSE (Clean Health Safety and Environment). And the community has good knowledge, attitudes and behavior in complying with the health protocols implemented. The conclusion of this research is that the implementation of health protocols at various tourist attractions in Jambi City has gone well with supervision carried out by the government and tourist owners.